Beyond the Rationality of Taste: Unpacking the Meaning of Identity in Papua People’s Culinary Design - M. I. Mambraku, Victor; Yanti Damayanti, Nuning; Martinus Pasaribu, Yannes; Nugraha, Adhi (Green Publisher Indonesia, 2025)
This study examines the relationship between the Agile Leadership development model, job stress, job satisfaction, and employee performance in distance higher education organizations. As the dynamics of the digital era force companies to adapt quickly, agile leadership becomes the key to improving organizational effectiveness. This study aims to explore the effect of Agile Leadership on job stress, job satisfaction, and employee performance, and how these three factors are interrelated. Using a quantitative approach and survey method on educators at Universitas Terbuka, the results of the study show that Agile Leadership has a significant effect on job stress, which in turn affects employee job satisfaction and performance. In addition, job satisfaction has been shown to have a positive effect on performance, which reinforces the importance of a flexible and adaptive leadership approach amidst uncertainty. These findings are expected to contribute to the development of a more agile and effective organizational model, as well as provide insight for managers and leaders in facing challenges in this fast-paced era.